2018
DOI: 10.1016/j.cub.2018.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Decodability of Reward Learning Signals Predicts Mood Fluctuations

Abstract: SummaryOur mood often fluctuates without warning. Recent accounts propose that these fluctuations might be preceded by changes in how we process reward. According to this view, the degree to which reward improves our mood reflects not only characteristics of the reward itself (e.g., its magnitude) but also how receptive to reward we happen to be. Differences in receptivity to reward have been suggested to play an important role in the emergence of mood episodes in psychiatric disorders [1, 2, 3, 4, 5, 6, 7, 8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 50 publications
(55 reference statements)
2
53
0
Order By: Relevance
“…We suggest the asymmetric effect we highlight can go some ways to explain a gradual evolution of an incremental impact of SSRIs on mood. Recent studies have shown that positive and negative surprise strongly impacts on self-reported affective states (Rutledge et al, 2014;Eldar & Niv, 2015;Eldar et al, 2018). Given a key role of surprise, our results explain how serotonergic intervention can, in principle, influence the affective experience of reinforcement.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…We suggest the asymmetric effect we highlight can go some ways to explain a gradual evolution of an incremental impact of SSRIs on mood. Recent studies have shown that positive and negative surprise strongly impacts on self-reported affective states (Rutledge et al, 2014;Eldar & Niv, 2015;Eldar et al, 2018). Given a key role of surprise, our results explain how serotonergic intervention can, in principle, influence the affective experience of reinforcement.…”
Section: Discussionsupporting
confidence: 56%
“…To fit the parameters of the different models to subjects' decisions, we used an iterative hierarchical expectation-maximization procedure across the entire sample, separately for each session (Bishop, 2006;Eldar et al, 2018). We sampled 10 5 random settings of the parameters from predefined prior distributions.…”
Section: Model Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…Using experience sampling (27,28) combined with functional neuroimaging, we show that intrinsic and extrinsic rewards contribute to affective dynamics (i.e., happiness). Recent studies demonstrate that computational approaches can quantify consistent relationships between subjective feelings and value-based decision-making (20,21,29,30), including in relation to individual social preferences (31). Here, using the same computational approach, applied in the context of a reinforcement learning task, we show that momentary happiness is influenced by both objectively quantifiable rewards and by intrinsic rewards, where the latter involves experiences with no inherent worth.…”
Section: Discussionmentioning
confidence: 76%